2019
DOI: 10.3892/mmr.2019.10230
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S regulates renal fibrosis in mouse models of mild and severe hydronephrosis

Abstract: As a member of the cysteine protease family, cathepsin S (CTSS) serves an important role in diseases such as cancer, arthritis and atherosclerosis. Nevertheless, its role in renal fibrosis is unknown. In the present study, the effects of CTSS on renal fibrosis in mild (group M) and severe (group S) hydronephrosis were studied by reverse transcription-quantitative PCR (RT-qPCR), western blot analysis (WB), Masson's trichrome staining and immunohistochemical staining in mouse models. The effects of CTSS on extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Levels of the mRNA, protein and activity of CTSS were found increased in the left ventricular myocardium of humans and rats with HF compared with controls, suggesting its participation in cardiac remodeling 65 . CTSS was also shown to affect epithelial-to-mesenchymal transition and ECM deposition in mouse models of mild and severe hydronephrosis, indicating its role in the regulation of renal fibrosis 66 .…”
Section: Discussionmentioning
confidence: 97%
“…Levels of the mRNA, protein and activity of CTSS were found increased in the left ventricular myocardium of humans and rats with HF compared with controls, suggesting its participation in cardiac remodeling 65 . CTSS was also shown to affect epithelial-to-mesenchymal transition and ECM deposition in mouse models of mild and severe hydronephrosis, indicating its role in the regulation of renal fibrosis 66 .…”
Section: Discussionmentioning
confidence: 97%
“…CTSS increases microvascular permeability and leukocyte adhesion during inflammation by activating protease-activated receptor (PAR)-2 on endothelial cells, leading to endothelial dysfunction (Steubl et al, 2017). Yao et al have confirmed that CTSS mediated the regulation of renal fibrosis through the transforming growth factor-β/SMAD signaling pathway (Yao et al, 2019). As GFR decreased, CTSS and markers of endothelial dysfunction associated with inflammation, such as soluble tumor-necrosis-factor receptors (sTNFR) 1 and 2, increased (Steubl et al, 2017) and might be crucial to MN pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It participates in the degradation of antiangiogenic peptides and adhesion proteins and promotes neovascularization and tumor cell invasion and metastasis ( 62 ). Previous studies found that CTSS can interact with MMPs and serine proteases and participates in the degradation of the ECM ( 63 , 64 ). An important physiological feature of the healing process after tissue injury is increased ECM synthesis and aggregation surrounding the wound.…”
Section: Discussionmentioning
confidence: 99%